The chameleon wore chartreuse : from the tattered casebook of Chet Gecko, private eye - Hale, Bruce (Hale, Bruce. Chet Gecko mystery., 2000)
When hired by a fellow fourth-grader to find her missing brother, Chet Gecko uncovers a plot involving a Gila monster's revenge upon the school football team.